Endogenous Money in the Age of Financial Liberalization - Gökçer Özgür; Korkut A. Ertürk (The University of Utah, Department of Economics, 2008)
The paper reports results that show a much weakened statistical relationship between total bank credit, total deposits and the broad money supply for the period after 1995 for the US, where no statistical causation can be discerned in either direction. This has been the result of the changing nature of the credit creation process where banks have acquired almost total independence from required reserves and core deposits in extending credit, and even an ability to circumvent the constraint posed by capital requirements through asset securitization, giving rise to an explosive increase in nonbank intermediation. As a result, the expansion of bank credit did not result in a commensurate increase of bank deposits because financial intermediation spilled over to nondepository institutions, and with the growing importance of nonbank deposits in M3, broad money supply became broader than banks' total deposits.
Keywords: B22; E12; E51; 330; Endogenous Supply of Money; Broad Money; Financial Intermediation; Asset Securitization